Pengaruh Harga, Kualitas, Promosi dan Pelayanan Terhadap Perilaku Konsumen Dalam Pembelian Produk Home Appliances Panasonic di PT. Sumber Karya Asia - Refina; Rikkie Dekas; Teguh Iman Santoso (Journal of Management, Entrepreneur and Cooperative, 2022)
ABSTRACT This study aims to examine the effect of Price, Quality, Promotion and Service on Consumer Behavior in purchasing Home Appliiances Panasonic products at PT. Asian Works Source. Multiple linear regression method. This study uses price, quality, promotion and service as independent variables and consumers behavior as the dependent variable. The data analysisi method of this study used qualitative and quantitative data analysis, and used descriptive research primary data was collected using a questionnaire distributed to respondents. The data analysis in this final projec uses multiple regression method and is processed with the SPSS 20 program. The results show that the price variable has a positive and significat effect on consumer behavior, the quality variable has a positiv and significat effect on consumer behavior. And the service variable has a positive and significant effect on consumer behavior in purchasing home Appliances Panasonic product at PT. Asian Works Source.